BRUGADA SYNDROME - Brugada, Ramon (The Methodist Hospital, Houston, Texas, 2014)
Brugada syndrome is a rare cardiac arrhythmia characterized by electrocardiographic right bundle branch block and persistent ST-segment elevation in the right precordial leads. It is associated with ventricular fibrillation and a high risk for sudden cardiac death, predominantly in younger males with structurally normal hearts. Patients can remain asymptomatic, and electrocardiographic patterns can occur both spontaneously or after pharmacological induction. So far, several pathogenic genes have been identified as associated with the disease, but SCN5A is the most prevalent one. Two consensus reports to define the diagnostic criteria, risk stratification, and management of patients have been published in the last few years. This brief review focuses on the recent clinical diagnosis, genetic basis, and advances in pharmacological treatment of Brugada syndrome.